Visitors’ perception on facilities and activities in Taman Bandar Jubli Perak Sultan Ahmad Shah Kuantan, Pahang - Mohd Liza, Nur Shahida Alisa (2019)
Taman Bandar Kuantan can be seen as an important recreational venue in Kuantan because of its strategic location in the heart of the city which attracts the residents. However, we still cannot identify what activities visitors do, how much they like the activity and how important they are to them. Meanwhile, we also do not know how important the facility is and their satisfaction with the facility and the visitors’ acceptance level of the entire area has yet to be known. As a result, is the place has its own charm to attract people to visit Taman Bandar Kuantan. Therefore, a study has been made to answer and solve all the problems because Taman Bandar Kuantan is a popular recreation area in Kuantan. The purpose for this study was to identify visitors’ perception on the importance and performance of the facilities in Taman Bandar Kuantan. This study also to relate the perception on the facilities and activities, with the interest between social demographic factors. The mean for all the importance and performance of facilities, and the importance and interest of activities were measured. A few social demographic factors were identified and some of them seem to affect a few perceptions on facilities and activities. Most important facility is outdoor exercise equipment and most satisfying facility is dustbin. Furthermore, jogging is the most importance and most interested activity at Taman Bandar Kuantan. Meanwhile, for the relationship, only age and marital status( ordinal factor) did not have significance on the importance and performance of facilities and only ethnic factor (nominal factor) does not have significance on the importance and interest level of activities.